Perceived Autonomy Support from Peers, Parents, and Physical Education Teachers as Predictors of Physical Activity and Health-Related Quality of Life among Adolescents-A One-Year Longitudinal Study - Henri Tilga; Hanna Kalajas-Tilga; Vello Hein; Lennart Raudsepp; Andre Koka (MDPI AG, 2021)
The current research adopts the trans-contextual model of motivation (TCM) to examine the role of perceived autonomy support from peers, parents, and physical education (PE) teachers on adolescents' autonomous motivation, intentions, and physical activity (PA) and health-related quality of life (HRQoL) over a one-year period. Adolescents (N = 264) aged between 11 and 15 years (M = 13.24; SD = 0.96) filled in relevant questionnaires during a four-wave longitudinal study. Perceived autonomy support from peers, parents, and PE teachers predicted PA (β ≥ 0.03, p < 0.009) and HRQoL (β ≥ 0.01, p < 0.009) mediated by constructs of TCM over a one-year period. The regressions of PA (β = 0.45, p < 0.001) and HRQoL (β = 0.56, p < 0.001) on themselves over a one-year period were significant. PA significantly predicted the HRQoL measured one year later (β = 0.20, p < 0.001), but not vice versa (β = 0.04, p = 0.52). The unidirectional cross-lagged relationship with the flow from PA to later HRQoL suggests that intervention programs focusing on promoting PA behaviour in adolescents should produce the most pronounced effects if their aim is also to promote HRQoL.